Invariant Entries and Gospel Lections in the Slavic Lectionary Menology of the 11–16th cc. (September) - Фаддеевна Ковязина, Надежда (Slavistica Vilnensis, 2000)
This article is devoted to the September lections of the Church Slavonic menology that have no significant variants in 36 lectionary gospel manuscripts of the 11–16th centuries. These standard lections form the structural basis that guarantees the integrity of this liturgical book, which is otherwise characterized by an extraordinarily large number of textual variants.